BIOELECTRICAL EVENTS IN EXCITABLE TISSUES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Excitable tissues-including neurons, skeletal muscle fibers, cardiac myocytes, and certain smooth muscle cells-generate and propagate bioelectrical signals fundamental to organismal function. These signals arise through voltage- and ligand-gated ion channels, ionic gradients maintained by ATP-dependent pumps, and dynamic changes in membrane capacitance and resistance. This article presents an expanded analysis of resting and dynamic membrane potentials, ionic fluxes, channel gating kinetics, electrotonic conduction, and tissue-specific electrophysiological specializations. Mathematical frameworks such as the Nernst, Goldman–Hodgkin–Katz (GHK), and Hodgkin–Huxley formulations are discussed. Tables summarize equilibrium potentials, gating variables, conduction velocities, pacemaker properties, and excitation–contraction coupling parameters. This work aims to provide a comprehensive, graduate-level overview of the biophysical principles governing excitability.